Legal innovation conversations about technology, the legal profession and societal change - Steffek, Felix 1975-; Sumida, Mihoko (Cambridge University Press, 2025)
Legal Innovation explores the impact of technology on the legal profession and societal change. Reflecting contributions from an international group of experts, the volume provides a comprehensive overview of the challenges and opportunities facing the legal profession today. With a particular focus on artificial intelligence, the book covers a wide range of topics, from dispute resolution and corporate governance to financial services and regulatory oversight. The conversational style of the chapters makes the content accessible while still maintaining academic rigor. This book is an essential read for policymakers, academics, lawyers, entrepreneurs, regulators and students who are interested in legal innovation and its impact on the legal profession as well as anyone interested in the intersection of law and technology.
"This book is a compilation of the lectures and discussions on legal innovation held at Hitotsubashi University in the year 2021. All contributions were updated in 2022 (with some additions in 2023) and further texts were added."
Keywords: Innovation; Rechtsfortbildung; Sozialer Wandel; Aufsatzsammlung